Automatic Tire Pressure Sensor at Petrol Pump - Mohd Isa, Nur Sabrina; Masek, Alias (Research and Innovation in Technical and Vocational Education and Training, 2024)
The average air pressure within each automobile tire is determined according to the specified range as stated for the Axia 1.0 AV model, which is 230 kPa per tire. Insufficient air pressure poses a high-risk. Failure to maintain the recommended tire pressure level led to significant consequences for the user. This is due in part to time constraints, which are one of the difficulties in determining tire pressure right at the initial stage. Therefore, this introduced project aims to design, develop, and implement testing for the functionality and usability of an Automatic Tire Pressure Detection System at Petrol Pump in order to address the aforementioned issue. The Design Thinking model, encompassing five phases of empathy, definition, ideation, prototyping and testing, was chosen to support a human-centered process as well as emphasizing three main aspects which are human, technology, and entrepreneurship. The installation of infrared sensors as car position detectors, as well as inductive sensors calibrated at specified height levels, capable of detecting low tire pressure when the sensor senses the car rim. The project results show that the product runs smoothly and meets the established objectives. Expert validation tests yield positive results, with experts suggesting continued product development by expanding the scope to include the development of an IoT system for the prototype that can recognize various vehicles with varying tire sizes. As a result, the developed product has been approved for commercialization in the industrial sector.